"Heroes' invisible wounds of war:" constructions of posttraumatic stress disorder in the text of US federal legislation. (January 2016) - Purtle, Jonathan
Abstract: Public policies contribute to the social construction of mental health problems. In this study, I use social constructivist theories of policy design and the methodology of ethnographic content analysis to qualitatively explore how posttraumatic stress disorder (PTSD) has been constructed as a problem in US federal legislation. I analyzed the text of 166 bills introduced between 1989 and 2009 and found that PTSD has been constructed as a problem unique to combat exposures and military populations. These constructions were produced through combat-related language and imagery (e.g., wounds, war, heroism), narratives describing PTSD as a military-specific phenomenon, and reinforced by the absence of PTSD in trauma-focused legislation targeting civilians. These constructions do not reflect the epidemiology of PTSD—the vast majority of people who develop the disorder have not experienced combat and many non-combat traumas (e.g., sexual assault) carry higher PTSD risk—and might constrain public and political discourse about the disorder and reify sociocultural barriers to the access of mental health services. Highlights: Public policies contribute to the social construction of mental health problems. A qualitative content analysis of US federal PTSD legislation was conducted. War-related language and imagery constructed PTSD as a military-specific problem. Military-specific constructions of PTSD do not reflect the disorder's epidemiology. Military-specific constructions could inhibit civilian access to PTSD treatment.